'You've Got No Support': The Experiences of Older Male Caregivers When Their Partner Enters Residential Care. Issue 5 (4th July 2022) - Fowler, Jamie; Blundell, Barbara; Morrisby, Claire; Hendrick, Antonia
ABSTRACT: This qualitative phenomenological study explored the experiences and needs of eight older male caregivers after their partner entered full-time residential aged care within the past 36 months. Semi-structured interviews were conducted, thematically analyzed, and member-checked for accuracy. This transition was a time of significant turmoil for caregivers. Feelings of grief, loss, guilt, and regret were experienced, intertwined with feelings of relief and reassurance that their partner would be well cared for within the care facility. Following the transition, caregivers also began thinking about building a new life. Helpful supports identified were friends and family, carer support groups, counseling services, and community support organizations. Participants described a need for further emotional support, assistance in understanding their partner's prognosis, and information about the expenses involved in entering residential care. It was suggested there is also a role for professional advisors or peer mentors to support male caregivers through this transition. Tailoring programs and services with consideration of the needs and experiences of older male caregivers will ensure that policies and programs are more supportive and responsive.